Child Vaccination and its Impacts on Health and Health Related Matters in Noakhali Region of Bangladesh - Tanna, Md Tanvir Haider; Ahmed, Jamiuddin; Debnath, Pankaj Chandra; Moghal, Md Mizanur Rahman; Hasan, Moynul (Bangladesh Pharmaceutical Journal, 2015)
This study was conducted to evaluate the rate of vaccination and its impacts on the children in four upazilas which were Noakhali sadar, Begumgonj, Companygonj and Chatkhil of Noakhali district. The study was carried out during the period of November 15, 2011 to December 15, 2011. Data were collected through questionnaire interviews, focus group discussions and cross check interviews. It was found that all interviewed parents of all ages and educational levels are aware about vaccination of their child. The study conducted on the rate of giving vaccines, (Tuberculosis, Polio, DPT, Measles and Hepatitis B) showed serious reactions in a few children after taking vaccine and occurrences of disease after taking the corresponding vaccine. The rate of vaccination in the four upazilas - Noakhali sadar, Begumgonj, Companygonj and Chatkhil were found to be 84, 86.6, 75.4 and 82%, respectively. No serious reactions were found among 120 children in four upazilas. Among thirty, two children suffered from Measles and one from Hepatitis B after taking the vaccine in sadar upazila. Three children suffered from Measles after Begumgonj and one suffered from Measles in Chatkhil. There were no children found to have a disease after taking the corresponding vaccination in Companygonj. Though the rate of vaccination in these areas is not so little the government should take necessary steps to ensure maximum rate of vaccination. DOI: http://dx.doi.org/10.3329/bpj.v16i2.22292 Bangladesh Pharmaceutical Journal 16(2): 125-129, 2013